The Unreasonable Efficiency of Total Rain Evaporation Removal in Triggering Convective Self‐Aggregation - Y.‐L. Hwong; C. J. Muller (Geophysical Research Letters)
Abstract The elimination of rain evaporation in the planetary boundary layer (PBL) has been found to lead to convective self‐aggregation (CSA) even without radiative feedback, but the precise mechanisms underlying this phenomenon remain unclear. We conducted cloud‐resolving simulations with two domain sizes and progressively reduced rain evaporation in the PBL. Surprisingly, CSA only occurred when rain evaporation was almost completely removed. The additional convective heating resulting from the reduction of evaporative cooling in the moist patch was found to be the trigger, thereafter a dry subsidence intrusion into the PBL in the dry patch takes over and sets CSA in motion. Temperature and moisture anomalies oppose each other in their buoyancy effects, hence explaining the need for almost total rain evaporation removal. We also found radiative cooling and not cold pools to be the leading cause for the comparative ease of CSA to take place in the larger domain.